Stakeholder influence in public sector information systems strategy implementation—The case of public hospitals in South Africa. (January 2018) - Hwabamungu, Boroto; Brown, Irwin; Williams, Quentin
Highlights: The paper responds to the call for greater emphasis on individuals (stakeholders) and what they do in the process of information systems strategy implementation. Public hospitals in developing countries are beset by problems related to lack of policy and strategy implementation and stakeholder dynamics which may impede implementation. Findings reveal that Information Systems (IS) strategy implementation in public hospitals involves a large and complex network of stakeholder groups at different levels, and over different time periods. These stakeholder groups act in accordance with formal and informal roles, rules and modalities. The relationships identified are captured in a Stakeholder Relations Influence (SRI) framework. The SRI framework can be assistive in the assessment and mapping of stakeholders and stakeholder relations, and the assessment of the implications of these relations for effective IS strategy implementation in public hospitals. Abstract: Recent literature on organisational strategy has called for greater emphasis on individuals (stakeholders) and what they do in the process of strategizing. Public sector organisations have to engage with an array of heterogeneous stakeholders in fulfilling their mandate. The public health sector in particular needs to engage with a diversity of stakeholders at local, regional and national levels when strategising. The purpose of this study is to investigate the influence of stakeholder relations on the implementation of Information Systems (IS) strategy in public hospitals in South Africa. An interpretive approach using two provinces was employed. The Activity Analysis and Development (ActAD) framework, an enhanced form of activity theory, was used as the theoretical framework. Data was collected using semi-structured interviews, meetings, documents analysis, physical artefacts and observation. The collected data was analysed using thematic analysis. Findings reveal that IS strategy implementation in public hospitals involves a large and complex network of stakeholder groups at different levels, and over different time periods. These stakeholder groups act in accordance with formal and informal roles, rules and modalities. Various contextual conditions together with the actions of, and interactions between stakeholder groups give rise to the situationality of stakeholder relations dynamics and strategy implementation. The multiple actions and interactions over time lead to the realisation of some aspects of the IS strategy in public hospitals. Given the complexity and dynamism of the context there are also certain unplanned implementations as well. These relationships are captured in a Stakeholder Relations Influence (SRI) framework. The SRI framework can be assistive in the assessment and mapping of stakeholders and stakeholder relations, and the assessment of the implications of these relations for effective IS strategy implementation in public hospitals. The framework can also provide the basis for the development of appropriate corrective measures in the implementation of strategies and policies in public institutions such as public hospitals.